Firm insoles effectively reduce hemolysis in runners during long distance running - a comparative study - Janakiraman, K.; Shenoy, S.; Sandhu, J. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2011)
Background Shock absorbing insoles are effective in reducing the magnitude and rate of loading of peak impact forces generated at foot strike during running, whereas the foot impact force during running has been considered to be an important cause of intravascular hemolysis in long distance runners. Objective of this study was to evaluate the intravascular hemolysis during running and compare the effect of two different types of insoles (Soft and Firm) on hemolysis. Methods Twenty male long and middle distance runners volunteered to participate in this study. We selected two insoles (Soft and Firm) according to their hardness level (SHORE 'A' scale). Participants were randomly assigned to the soft insole (group 1) and firm insole (group 2) group with ten athletes in each group. Each athlete completed one hour of running at the calculated target heart rate (60-70%). Venous blood samples were collected before and immediately after running. We measured unconjucated bilirubin (mg/dl), lactate dehydrogenase (µ/ml), hemoglobin (g/l) and serum ferritin (ng/ml) as indicators of hemolysis. Results Our study revealed a significant increase in the mean values of unconjucated bilirubin (P < 0.05) while running with soft insoles indicating the occurrence of hemolysis in this group of athletes. Graphical analysis revealed an inverse relationship between hardness of insoles and hemolysis for the observed values. Conclusion Our results indicate that intravascular hemolysis occurs in athletes during long distance running and we conclude that addition of firm insoles effectively reduces the amount of hemolysis in runners compared to soft insoles.